IMPLEMENTASI PROGRAM PENGEMBANGAN USAHA KESEHATAN SEKOLAH (UKS) DI SD NEGERI 017 SUNGAI GANTANG KECAMATAN KEMPAS - KABUPATEN INDRAGIRI HILIR - jurnalmap map (Program Pascasarjana Universitas Wijaya Putra Surabaya, 2022)
The purpose of this study is to determine the implementation of the school health business program (UKS), to determine the results of health services in the UKS program and to determine the results of fostering a healthy school environment in the UKS program at SD Negeri 017 Sei Gantang, Kempas District, Indragiri Hilir Regency. Qualitative research is a study aimed at describing and analyzing phenomena, events, social activities, attitudes, beliefs, perceptions, thoughts of people individually and in groups. The unit of analysis in this study were all students and teachers who handled UKS SD Negeri 017 Sei Gantang, Kempas District. Indragiri Hilir Regency. Data collection methods were interview methods, observation methods and documentation methods The results of the research and data analysis explain that 1) The implementation of the school health business program (UKS) at SD Negeri 017 Sei Gantang, Kempas District, Indragiri Hilir Regency has been going well, but not yet optimal; 2) Health services in the UKS program at SD Negeri 017 Sei Gantang, Kempas District, Indragiri Hilir Regency are not optimal. 3) The development of a healthy school environment in the UKS program at SD Negeri 017 Sei Gantang, Kempas District, Indragiri Hilir Regency has not been optimal.